The Economic Consequences of Urban Decentralisation and Centralisation in the Light of Foreign Literature - Lityński, Piotr (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The paper looks at theory covered in the foreign literature in English on the economic costs and benefits of urban centralisation and decentralisation. A definitional approach to these two concepts is presented, as is the methodological basis for assessing their economic efficiency. The economic costs and benefits of decentralisation processes and the implementation of centralisation are catalogued. The concepts of urban sprawl and the compact city were used as examples of the determination of the costs and benefits.